Analisis Efektivitas Pemeriksaan Pajak Di Masa Pandemi Covid 19 Dalam Rangka Meningkatkan Target Penerimaan Pajak Studi Kasus Pada KPP Pratama Jakarta Pasar Rebo - Elisa Andriani a; Notika Rahmi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Taxes are obligations that must be paid by the public, both individuals and entities, from their income or income for the government. During the Covid-19 pandemic, mobility is disrupted and has an impact on tax audits. This study aims to analyze the effectiveness of tax audits during the Covid-19 pandemic in order to increase the target of tax revenue, a case study at KPP Pratama Jakarta Pasar Rebo. Data collection techniques in this study were conducted by means of interviews, observation and documentation. Technical data analysis in this study was carried out by means of qualitative descriptive research. The results of this study indicate that inspections during the COVID-19 pandemic are considered ineffective because there are inhibiting factors that occur during tax audits such as PCR or swab tests before entering the company, incomplete tax documents, termination of finance/tax employees due to income. decreased during the COVID-19 pandemic. During the COVID-19 pandemic, the efforts made by the KPP Pratama Jakarta Pasar Rebo were very optimal, inspections were carried out online such as zoom meetings. Inspection documents can also be sent via email or through the post office etc.